(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
With technology becoming the current convenience for conducting online marketing processes, various companies have used the internet to make it easier for people to buy their products and their partner products through online shopping sites. In this research, the writer takes the title "The Effect of E-Service Quality and Brand Trust on the Repurchase Intention of Adrsfootwear Products at Bukalapak.com." The purpose of this study was to determine the influence of e-service quality and brand trust on repurchase intentions for Adrs Footwear products. The research method uses descriptive and verification by collecting data through observation and questionnaire, where the population of 8134 uses a solving formula with a tolerance level of 10%, then the population is 99. The results of the analysis of E-Service Quality, Brand Trust, and Intention to Buy Back Adrsfootwear Products are necessary to increase customer satisfaction with E-service quality so as to create brand trust towards product sales compared to other competitors by increasing repurchase interest in Adrsfootwear at bukalapak.com. Based on the results of the correlation test, the effect of E-Service Quality and Brand Trust on Repurchase Intention has a significant positive level and shows a very strong relationship, and the results of hypothesis testing using the F test can be accepted because the calculation results on Ftable > Fcount mean Ho is rejected and Ha is accepted.